1998
DOI: 10.1177/019262339802600504
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Differences in Renal Localization of Cyclooxygenase Isoforms: Implications in Nonsteroidal Antiinflammatory Drug-Related Nephrotoxicity

Abstract: Cyclooxygenase (COX) exists in 2 related but unique isoforms: one is constitutive (COX-1) and functions in normal cell physiology, and the other is inducible (COX-2) and is expressed in response to inflammatory stimuli. Nonsteroidal antiinflammatory drugs (NSAIDs) cause renal toxicity following inhibition of renal cyclooxygenases. Humans and animals exhibit differences in susceptibility to NSAID-related renal toxicity, which may be associated with differences in expression of 1 or both isoforms of COX in the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
154
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(165 citation statements)
references
References 33 publications
5
154
0
3
Order By: Relevance
“…The ketoprofen group grade was higher than that of the control group, which indicates that fecal occult blood tests may be useful for detection of gastrointestinal bleeding disorders in dogs treated with NSAIDs. Adverse renal effects of NSAIDs result primarily from the decreased synthesis of renal vasodilative PGs (PGE2 and PGI2) [1,3,19,27]. A previous study of ketoprofenassociated adverse renal effects found decreased endogenous creatinine clearance in dogs receiving ketoprofen before castration surgery [8].…”
Section: Discussionmentioning
confidence: 99%
“…The ketoprofen group grade was higher than that of the control group, which indicates that fecal occult blood tests may be useful for detection of gastrointestinal bleeding disorders in dogs treated with NSAIDs. Adverse renal effects of NSAIDs result primarily from the decreased synthesis of renal vasodilative PGs (PGE2 and PGI2) [1,3,19,27]. A previous study of ketoprofenassociated adverse renal effects found decreased endogenous creatinine clearance in dogs receiving ketoprofen before castration surgery [8].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Immunohistochemical localization studies have detected COX-2 in the perimacula densa region and a subset of thick ascending limb (TAL) epithelial cells located in the cortex (cTAL) 6,7 and outer medulla (mTAL) 7 as well as in interstitial medullary cells. 8 COX-2 expression in the kidney under basal conditions suggests that COX-2 may have a physiological role. Expression of the COX-2 isoform is increased in the kidney during development, 9,10 adrenalectomy, 11,12 and low-salt diet 13 ; it is decreased by glucocorticoids.…”
mentioning
confidence: 99%
“…Kay-Mugford et al reported that MadinDarby canine kidney cells expressed both COX-1 and COX-2 [21]. Furthermore, COX-2 is sparsely expressed in the macula densa of the normal dog kidney, and up-regulation of COX-2 in the kidney and the stomach [16] has also been reported by several studies in dogs with volume or salt depletion; these results suggest that COX-2 and COX-1 have a possible role in the response that helps maintain renal function [3,22,40]. Thus, it is thought that ketoprofen inhibits mainly COX-1 in the kidney and that prednisolone may concomitantly block up-regulation of COX-2 that helps maintain renal function, which results in a decrease of RPF and GFR and causes the renal tubular injuries and hyperalbuminuria, which are early marker of renal disease in dogs [12,13,25].…”
Section: Disccusionmentioning
confidence: 78%